Enhancing Entrepreneurial Orientation Research: Operationalizing and Measuring a Key Strategic Decision Making Process - Lyon, Douglas W.; Lumpkin, G. T.; Dess, Gregory G. (Journal of Management, 2000)
As a means to enhance prescriptive theory on a firm’s entrepreneurial orientation, this paper addresses the strengths and weaknesses of three approaches to measurement: managerial perceptions, firm behaviors, and resource allocations. We examine a set of recent studies employing these approaches, propose important contingencies regarding their use, and suggest that measurement accuracy can be improved by using a triangulation of methods. The paper concludes with a discussion of theoretical, resource availability, and interpretability considerations in measurement selection.